The Income Tax : How progressive should it be? - Galvin, Charles O. (Washington D.C. : American Enterprise Institute for Public Policy Research, 1969)
The book presents the views of two distinguished tax experts at the Rational Debate Seminars for 1969. Both are eminent scholars widely known in the taxation field.
osc 3/7/17
Loans
Keywords: Taxation